2015
DOI: 10.1111/apm.12377
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of variants of pegylated interferon alpha in treatment of chronic HCV patients

Abstract: HCV infection presents a vast burden in the regions of high prevalence such as Egypt, where most HCV isolates are genotype 4b. Combined treatment of three variants of pegylated interferon and ribavirin is still the standard of care in Egypt. However, no conclusive data confirming their efficacy are available. Here, 60 chronic HCV patients were randomized for ribavirin plus Peg Intron (PEG-IFNα-2b), Pegasys (PEG-IFNα-2a) or Reiveron Retard (PEG-IFNα-2a). Serum interferon and antibody (Ab) levels were measured, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Indeed, a number of Egyptians started new DAA regimen (with/out IFN/RBV), including (a) ledipasvir-sofosbuvir for 12 weeks, (b) ombitasvir-paritaprevir-ritonavir plus ribavirin for 12 weeks, or (c) sofosbuvir plus ribavirin for 24 weeks [ 27 ], with the government covering expenses of 80% of patients, treating 5 million patients of an estimated 11 million infected people will still cost Egypt $4·5 billion of the $5.4 billion total health budget for 2016–17 [ 30 , 31 ]. A recent study indicated that Pegasys may be a superior choice of interferon therapy under low socioeconomic conditions [ 32 ]. Thus, in Egypt, PEG-IFN remains an integral part of treatment [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a number of Egyptians started new DAA regimen (with/out IFN/RBV), including (a) ledipasvir-sofosbuvir for 12 weeks, (b) ombitasvir-paritaprevir-ritonavir plus ribavirin for 12 weeks, or (c) sofosbuvir plus ribavirin for 24 weeks [ 27 ], with the government covering expenses of 80% of patients, treating 5 million patients of an estimated 11 million infected people will still cost Egypt $4·5 billion of the $5.4 billion total health budget for 2016–17 [ 30 , 31 ]. A recent study indicated that Pegasys may be a superior choice of interferon therapy under low socioeconomic conditions [ 32 ]. Thus, in Egypt, PEG-IFN remains an integral part of treatment [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The peginterferon αA2 the patient was given on day 8 might have influenced his plasma interferon-α levels ( 6 ). However, a previous study also showed increased levels of interferon-α in a patient who survived MERS-CoV infection but not in a person who died of MERS ( 7 ).…”
mentioning
confidence: 99%
“…Several articles have claimed that PegIFN-α-2a provides a better outcome than PegIFNα-2b [8][9][10], whereas many others report no difference in outcomes [11][12][13]. Although the relative efficacies of different forms of PegIFN-α are still debated, the results in current study reveal that neither SVR rate nor the variation of mental health status, differed between patients who were treated with PegIFN-α-2a (Group A) and those who were treated with PegIFN-α-2b (Group B).…”
Section: Researchmentioning
confidence: 99%
“…Differences between these two PegIFN-α preparation include molecular weight, subtype of human IFN-α, pharmacokinetic profile (especially half-life) and pharmacodynamic gap [6,54,55]. PegIFN-α-2a is a long-acting interferon; is monopegylated with a 40kDa branched PEG moiety, and comprises four major positional isomers that involve Lys31, Lys121, Lys131, and Lys134 of interferon-α-2a [8][9][10]. We hypothesize that the unique pharmacological profile of PegIFN-α-2a may be related to the increase in serum levels of cytokines at week 24; however, the mechanism by PegIFN-α-2a and -2b differently alter pro-inflammatory cytokine levels warrants further study.…”
Section: Antiviral Treatment Pro-inflammatory Cytokines and Bdnfmentioning
confidence: 99%
See 1 more Smart Citation